Immunogenicity against wild-type and Omicron SARS-CoV-2 after a third dose of inactivated COVID-19 vaccine in healthy adolescents - Leung, Daniel; Cohen, Carolyn A.; Mu, Xiaofeng; Rosa Duque, Jaime S.; Cheng, Samuel M. S.; Wang, Xiwei; Wang, Manni; Zhang, Wenyue; Zhang, Yanmei; Tam, Issan Y. S.; Lam, Jennifer H. Y.; Chan, Sau Man; et al. (Frontiers in Immunology, 2023)
Two doses of inactivated SARS-CoV-2 vaccine CoronaVac cannot elicit high efficacy against symptomatic COVID-19, especially against the Omicron variant, but that can be improved by a third dose in adults. The use of a third dose of CoronaVac in adolescents may be supported by immunobridging studies in the absence of efficacy data. With an immunobridging design, our study (NCT04800133) tested the non-inferiority of the binding and neutralizing antibodies and T cell responses induced by a third dose of CoronaVac in healthy adolescents (N=94, median age 14.2 years, 56% male) compared to adults (N=153, median age 48.1 years, 44% male). Responses against wild-type (WT) and BA.1 SARS-CoV-2 were compared in adolescents. Safety and reactogenicity were also monitored. A homologous third dose of CoronaVac further enhanced antibody response in adolescents compared to just 2 doses. Adolescents mounted non-inferior antibody and T cell responses compared to adults. Although S IgG and neutralizing antibody responses to BA.1 were lower than to WT, they remained detectable in 96% and 86% of adolescents. T cell responses to peptide pools spanning only the mutations of BA.1 S, N and M in adolescents were preserved, increased, and halved compared to WT respectively. No safety concerns were identified. The primary vaccination series of inactivated SARS-CoV-2 vaccines for adolescents should include 3 doses for improved humoral immunogenicity.